Qur'anic Perspective on Children’s Moral Decline in the Digital Era: A Study of Q.S. Al-Isra: 23–24 - Muh. Ibnu Sholeh; Ibnu Imam Al Ayyubi; Lutfiyah Firdaus; Engr. Imran Arshad; Tovi Primaresty (Al-Bustan: Jurnal Pendidikan Islam, 2025)
The digital era brings challenges in children's moral education, especially in instilling ethical and moral values in accordance with Islamic teachings. This study aims to analyse the application of children's moral education based on Q.S. Al-Isra: 23-24 in facing the challenges of the digital era. The research method used is qualitative with an interview approach to parents, educators, and scholars. The results showed that the main challenge in children's moral education in the digital era is the influence of technology that can reduce social interaction and politeness values. The strategies implemented include parental role modelling, limiting and monitoring the use of technology, as well as strengthening communication and prayer. The findings confirm that moral education based on Islamic values needs to be strengthened through synergy between family, school and the digital environment so that children continue to have good character. This research provides recommendations to optimise the use of technology as an educational tool that supports children's moral education in the modern era. Therefore, policies and educational programmes are needed for parents and educators to guide children in the wise use of technology and instil strong moral values in accordance with Islamic teachings. Thus, moral education for children based on Q.S. Al-Isra: 23-24 in the digital era not only plays a role in shaping noble individuals but also becomes a long-term investment in creating a better generation that adheres to Islamic values in modern life.